Effect of Celebrity Endorser and Brand Image on Purchasing Decision For Scarlett Whitening Product - Eka Putri, Septia Vindy; Widodo, Joko; Zulianto, Mukhamad (Jurnal Ekonomi Balance, 2023)
The purpose of this study was to determine the effect of celebrity endorser and brand image on purchasing decisions for Scarlett Whitening products on students of Economic Education, Faculty of Teacher Training and Education, University of Jember, batch 2018-2021 simultaneously and partially. This research uses correlational quantitative research with the aim of seeing the influence of independent variables on the dependent variable. The sampling technique used in this study is populative sampling , namely 87 students of Economics Education, Faculty of Teacher Training and Education, University of Jember class 2018-2021 who have purchased Scarlett Whitening products. Questionnaire and interview methods were used to collect data. The data analysis technique in this study used multiple linear analysis, regression line variance, F test, T test, coefficient of multiple determination, effectiveness of multiple linear regression lines and standard error of the estimates. The results of the study explain that simultaneously and brand image have a positive and significant effect on purchasing decisions for Scarlett Whitening products, while partially celebrity endorsers have a significant effect on purchasing decisions and brand image has a significant effect on purchasing decisions for Scarlett Whitening products.